A PROTEIN CONCENTRATE DERIVED FROM MESENCHYMAL STEM CELLS (MSC-PC) INDUCES EPITHELIALIZATION OF A CHRONIC WOUND IN A DOG - CASE REPORT - Alvarenga, M. (2021)
Univ Estadual Paulista, Fac Med Vet & Zootecnia, Vet Surg & Anim Reprod, Campus Botucatu, Botucatu, SP, Brazil